Agricultural exports and retaliatory trade actions: An empirical assessment of the 2018/2019 trade conflict. Issue 2 (7th January 2021) - Grant, Jason H.; Arita, Shawn; Emlinger, Charlotte; Johansson, Robert; Xie, Chaoping
Abstract: We estimate the ex‐post agricultural trade impacts of retaliatory measures imposed by foreign countries in response to United States' Section 232 and 301 tariffs using a theoretically consistent, monthly, product line gravity equation. Retaliation led to significant US agricultural export losses of 13.5 to 18.7 billion on an annualized basis. Considerable heterogeneity exists in the average treatment effect of retaliation. First, retaliatory trade actions presented a strong within‐year seasonal impact. Nearly 70% of aggregate trade losses occurred during the US's peak export marketing season. Second, U.S. trade losses were particularly pronounced on homogeneous bulk commodities, whereas product differentiation dampened the impact of retaliation. Third, with few exceptions, the counterfactually estimated direct trade losses line up well with the U.S. Department of Agriculture's (USDA) trade damage estimates for trade aid programs distributed to farmers impacted by the trade dispute. Finally, we find little evidence that U.S. exports were able to be reoriented to alternative, nonretaliating markets—an indication of high bilateral trade frictions and the destructive consequences of retaliatory trade actions.